Enhanced dechlorination of an enzyme-catalyzed electrolysis system by ionic liquids: Electron transfer, enzyme activity and dichloromethane diffusion. (October 2021) - Wu, Meng; Hu, Jun; Wu, Yuexin; Tang, Yuwei; Zhang, Yan; Guan, Yanhong; Lou, Zimo; Yu, Zhiliang; Yu, Jianming
Abstract: Enzyme-catalyzed electrolysis system (EES) is a promising technique for the efficient dechlorination of pollutants. In this study, ionic liquids (ILs) was first introduced to enhance the dichloromethane dechlorination performance of an EES. An imidazole-based IL, 1-ethyl-3-methylimidazole tetrafluoroborate ([EMIM][BF4 ]), was chosen due to its excellent performance on dechlorination enhancement than other three ILs. The cyclic voltammograms with different scan rates shows that the presence of IL increased the apparent electron transfer rate constant ( k s ) from 0.008 to 0.013 s −1 . The calculated surface electroactive species concentration ( τ c ) also increased from 7.8 × 10 −9 to 9.5 × 10 −9 mol cm −2 . Electrochemical impedance spectroscopy analysis illustrates that the IL mainly weakened the interfacial resistance between electrolyte and cathode to accelerate the electron communication in the EES. The introduction of IL facilitated the regeneration of reduced glutathione from oxidized glutathione, whereas inhibited the catalytic activity of dehalogenase via the disruption of secondary structure shown in circular dichroism spectra. The presence of IL was also facilitated the dichloromethane diffusion from electrolyte to cathode. The mass transfer rate constants of dichloromethane ( k m, d ) increased by 6.9 times after the addition of IL. The optimum volume concentration, pH value, reaction temperature and applied voltage were 20%, 7, 35 °C and −0.8 V vs Ag/AgCl, respectively. The study is helpful to understand the promotion mechanism of IL on the dechlorination performance of EES when it is adopted as a treatment technique. Graphical abstract: Image 1 Highlights: [EMIM][BF4 ] was selected to enhance the dechlorination performance of the EES. The IL increased the electron transfer rate and surface electroactive substances. The IL accelerated the GSH regeneration, while inhibited the dehalogenase activity. The IL promoted the mass transfer rate constant of dichloromethane by 6.9 times. IL concentration, pH, temperature and voltage affected dechlorination performance.